STUDY OF CLEAN AND HEALTHY LIFE BEHAVIOR OF ELEMENTARY SCHOOL STUDENTS AT SCHOOLS APPLYING ADIWIYATA PROGRAM AT STATE ELEMENTARY SCHOOL IN PRIGEN PASURUAN - Iis Fatimawati (UNEJ e-Proceeding, 2017)
Background: Clean And Healthy Life Behavior (CHLB) in schools can be pursued by the adiwiyata school program. Students who play a role active on Clean And Healthy Life Behavior (CHLB) can realize healthy school. This research was intended to explain the difference of CHLB students in schools that implement and not implement adiwiyata school program. Methods: This study used analytic-comparative method with Cross Sectional approach. The sample of this research was students of SDN Gambiran I as many as 53 students and SDN II Prigen as many as 29 students with cluster random sampling technique. The independent variable was the Adiwiyata school status and the dependent variable was the student’s CHLB. The instruments used were CHLB questionnaires and observation sheets of school sanitation and canteen facilities. Results: The results showed that Mean value of CHLB in SDN Gambiran I was 135.96 with CHLB average of 81.41%. Mean value of CHLB in SDN II Prigen was127.17 with CHLB average of 76.15%. Independent T Test obtained ρ = 0.08 with α = 0,05 (ρ <α) means that there are was significant difference of CHLB in both schools. Conclusions: From the results this research. the researcher suggests the coaching of healthy behavior so that the clean and healthy life behavior of students is well established by adding understanding and knowledge to the Elementary school students especially those that have not implemented the adiwiyata school program. Keywords: Elementary school, Adiwiyata program, Clean and healthy life behavior